Two-signal electrochemical detection system for evaluation viability of Staphylococcus aureus. (20th January 2021) - Wang, Zhong; Gao, Hongfu; Cui, Jiwen; Zhou, Shi; Zhao, Yanli; Ye, Cai; Li, Jinlian; Wu, Dongmei
Highlights: Two electrochemical signals of S. aureus suspension were detected. The electrochemical signals of S. aureus were attributed to adenine and guanine. Microbial viability was evaluated from the perspective of purine metabolism. The inhibition of bacterial viability was evaluated by purine metabolism. Abstract: Establishment of new method for evaluation microbial viability has become an urgent need in the fields of biology, medicine, environment and so on. In this paper, two electrochemical signals of Staphylococcus aureus ( S. aureus ) at + 0.693 and + 0.973 V vs. Ag/AgCl ( sat . KCl) were detected on the multi-walled carbon nanotube modified glassy carbon electrode (MWCNTs/GCE), and attributed to the oxidation of guanine and adenine secreted by S. aureus . For the first time, bacterial viability was evaluated from the perspective of proliferation and purine metabolism. Compared with the plate counting method, the electrochemical signals of guanine and adenine showed an earlier change of viability when S. aureus entered stationary from logarithmic phase and apoptotic from stationary phase during the growth process of S. aureus . There were good linear relationships between electrochemical signals of guanine and adenine and the number of S. aureus cells in different growth phases, but there were different detection thresholds. At the logarithmic phase, S. aureu s had stronger viability and ability to metabolize purines, which resulted in a lower detection threshold. Both electrochemical signals of bacteria could well reflect the inhibition of levofloxacin on S. aureus viability, and the guanine signal peak was closer to the result of plate counting method. Graphical abstract: Image, graphical abstract